6x+7=3+4x-4x-7

Simple and best practice solution for 6x+7=3+4x-4x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7=3+4x-4x-7 equation:


Simplifying
6x + 7 = 3 + 4x + -4x + -7

Reorder the terms:
7 + 6x = 3 + 4x + -4x + -7

Reorder the terms:
7 + 6x = 3 + -7 + 4x + -4x

Combine like terms: 3 + -7 = -4
7 + 6x = -4 + 4x + -4x

Combine like terms: 4x + -4x = 0
7 + 6x = -4 + 0
7 + 6x = -4

Solving
7 + 6x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 6x = -4 + -7

Combine like terms: 7 + -7 = 0
0 + 6x = -4 + -7
6x = -4 + -7

Combine like terms: -4 + -7 = -11
6x = -11

Divide each side by '6'.
x = -1.833333333

Simplifying
x = -1.833333333

See similar equations:

| -6a=0 | | -1/18=n-8/9 | | 9+n=10 | | 2+k=8/3 | | d+2/9=-88/9 | | w-3/4=-1/6 | | n+1/2=5/4 | | n-9=-101/11 | | 13/28=n+5/7 | | b+7=31/5 | | 1/3d=-4 | | b-2=-15/11 | | a/4=-1 | | 2/3k=-6 | | b+1/2=23/2 | | 4+d=9 | | -2/3d=-2/7 | | 2t=6 | | -23/6=b-3 | | k+6=10 | | a+3/4=-5/36 | | a+8=25/3 | | a+6/7=51/35 | | 1/5+b=-2/5 | | n+1/2=-21/2 | | 53/6=x+5/6 | | n+5=65/12 | | t+6/7=13/7 | | k+5=19/4 | | w+4/5=-21/5 | | w+5/6=65/6 | | 17/18=d+4/9 |

Equations solver categories